Competitiveness Rice Farming In Sragen Regency - Cecep Suhardedi; Dwidjono Hadi Darwanto; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
Rice is indonesian agriculture major crop. Indonesian rice historically has been the primary staple food and is an important economic driver and cultural symbol. On the basis of Sragen regency is one of the major rice producer in Central Java. This research aims to determine the level of private and social profi tability and competitiveness of rice farming in Sragen regency. Policy analysis matrix (PAM) is the approach used to determine the level of profitability and competitiveness of rice farming in Sragen Regency. Sampling conducted by Simple Random Sampling of the 20 districts in Sragen which are rice production area. The results show that the value of profi t for private and social is IDR 9.989.911,16 and IDR 4.273.004,18 respectively. Rice farming in Sragen Regency is profi table and feasible to cultivate. Two indicators to measure the competitiveness were Private Cost Ratio (PCR) which later shows that rice farming in Sragen Regency is more competitive as the PCR < 1, and Domestic Resources Cost Ratio (DRCR) shows that the rice farming has a comparative advantage as the DRCR < 1.